2009
DOI: 10.1590/s0001-37652009000300019
|View full text |Cite
|
Sign up to set email alerts
|

Human neutrophil alloantigens systems

Abstract: Neutrophil alloantigens are involved in a variety of clinical conditions including immune neutropenias, transfusionrelated acute lung injury (TRALI), refractoriness to granulocyte transfusions and febrile transfusion reactions. In the last decade, considerable progress has been made in the characterization of the implicated antigens. Currently, seven antigens are assigned to five human neutrophil antigen (HNA) systems. The HNA-1a, HNA-1b and HNA-1c antigens have been identified as polymorphic forms of the neut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 46 publications
(31 reference statements)
0
38
0
Order By: Relevance
“…, neutrophils) to the affected area as a hallmark of acute inflammation. 44 CD11b is a canonical surface marker of myeloid cells including monocytes, macrophages, and neutrophils 45,46 Our FACS analysis showed that the percentage of CD11b + subpopulation cells among the CD45 + CD54 + population was notably increased in S-GO-treated mice (56%) and L-GO-treated mice (69%), compared to untreated mice (30%) (Figure 3K, P < 0.05). The number of CD11 b + subpopulation among the CD45 + CD54 + cells was strikingly increased by more than 90-fold for S-GO and 129-fold for L-GO, compared to untreated mice (Figure 3L, P < 0.001).…”
Section: Resultsmentioning
confidence: 91%
“…, neutrophils) to the affected area as a hallmark of acute inflammation. 44 CD11b is a canonical surface marker of myeloid cells including monocytes, macrophages, and neutrophils 45,46 Our FACS analysis showed that the percentage of CD11b + subpopulation cells among the CD45 + CD54 + population was notably increased in S-GO-treated mice (56%) and L-GO-treated mice (69%), compared to untreated mice (30%) (Figure 3K, P < 0.05). The number of CD11 b + subpopulation among the CD45 + CD54 + cells was strikingly increased by more than 90-fold for S-GO and 129-fold for L-GO, compared to untreated mice (Figure 3L, P < 0.001).…”
Section: Resultsmentioning
confidence: 91%
“…Antibodies (Abs) against human neutrophil antigen (HNA) have been linked to alloimmune neonatal neutropenia, autoimmune neutropenia and transfusion-related acute lung injury (TRALI) [1,2]; several detection systems for HNA Abs have been developed [3,4]. Although the International Granulocyte Immunology Workshop recommends using a combination of the granulocyte immunofluorescence test (GIFT) and granulocyte agglutination test (GAT) [5], it can still be difficult to determine antibody specificity in some cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we developed two new systems-the MAIGA system using KY cells and the KY cell-based, but MoAb-independent antigen capture system-and investigated whether these systems could be used to detect HNA Abs, focusing on HNA-1a Abs, which causes TRALI and is the most frequently detected Ab in autoimmune neutropenia [18][19][20]. Additionally, we evaluated the usefulness of LABScreen Multi, the only commercial system for HNA Ab detection currently available.…”
Section: Introductionmentioning
confidence: 99%
“…Subsets of human circulating neutrophils have been identified under steady-state conditions based on their expression of CD177 or OLFM4 and linked them with autoimmunity 43, 44 . It should be noted that there is considerable variability in CD177 expression within the population and it is not expressed by all individuals 45 . Pro-angiogenic neutrophils that are CD49d + VEGR1 hi CXCR4 hi are also present in low quantities in both mouse and human blood and are recruited in response to VEGF-A 46, 47 .…”
Section: Neutrophil Heterogeneity and Plasticitymentioning
confidence: 99%